Technology of forming of tubular cable lugs for connection to the switchgear - Kubit, Andrzej; Kluz, Rafał (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2016)
Tubular cable lugs are used to connect the switchgear. This type of cable lugs increase the safety, reliability, connectivity and ease of installation. Due to the requirement to ensure high conductivity and durability of the connection are made of copper alloys. New solutions of modular switchgear make it necessary to change the structure of tubular cable lugs, associated with the need to produce the coupling of the tapered section of the contact. The required shape is obtained by machining, which process is not cost-effective and involves a high cost of a technical embodiment of the device, due to significant losses of material. This paper describes a new technology tubular cable lugs based fully on the plastic working, which makes this technology very favorable from the viewpoint of material savings. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)